A new genus and species in the diverse dung beetle tribe Onthophagini Streubel, 1846 (Scarabaeidae: Scarabaeinae) from South Africa - Deschodt, Christian M.; Sole, Catherine L. (Zootaxa, 2023)
A new dung beetle genus and species is described and pictured following its recent discovery on a farm in South Africa. Hathor spinosa Deschodt, new species belongs to the subfamily Scarabaeinae, tribe Onthophagini Streubel, 1846, it shows a unique set of characters. A map is provided to show the type locality of the new genus and species that has a putative association with ants.